Study of Materials Science of Eulaliopsis binata Fiber with an Overview on Its Sustainable Economic Prospects as a Non-timber Forest Product - Adhikari, Hari Sharan; Krishnamoorthy, Ganesan; Adhikari, Rameshwar (Journal of Engineering and Sciences, 2025)
The present study demonstrates that Babiyo (Eulaliopsis binata) leaves, a grass of Poaceae family, produce commercially viable fibers with multifaceted applications. It is a plant of high resilience to climatic adversities and soil infertility, and a strong root system to prevent erosion. The morphological studies via field emission scanning electron microscopy (FE-SEM) revealed that E. binata fibers with high cellulose content could essentially be used to prepare high-quality paper and fiber-based utility items, and it could lend itself as a reinforcement material to be incorporated in a polymer matrix to give high-performance composite materials customized mechanical and tribological applications. The energy dispersive X-ray spectroscopy (EDX) analyses showed the abrasion-resistant surface of the fiber due to almost consistent distribution and interactive dispersion of silicon, carbon, oxygen, nitrogen, sodium, magnesium, silicon, phosphorus, sulfur, potassium, calcium, iron atoms throughout the fiber structure. The powder X-ray diffraction (PXRD) study showed the fiber surfaces' crystalline behavior (crystallinity index 30.02%). The literature shows that E. binata methanolic extract contains flavonoids and phenolic compounds with anti-oxidant behavior, owing to which the extract brings about an increase in the reduced level of natural in vivo and in vitro glutathione (GSH) level. The E. binata extracts show the healing of wounds, antibacterial activity and anti-ailment behavior in dermatological diseases. The toxicological study of n-hexane, ethyl acetate and methanolic extracts of E. binata shows no detrimental effects to vital organs. At this juncture, the E. binata cultivation, fiber processing, and industrialization are crucial towards the sustainable economic growth of rural people, revenue generation, soil conservation initiatives, and the utilization of non-timber forest product (NTFP) resources.